SISTEM BAGI HASIL PRODUKSI TAMBAK BANDENG DALAM MASYARAKAT SUKA JAYA KECAMATAN MUARA TIGA MENURUT HUKUM ISLAM - Safriadi Safriadi (Jurnal Tahqiqa : Jurnal Ilmiah Pemikiran Hukum Islam, 2019)
This study examines "The Syirkah System in Pond Management IsViewed According to Islamic Law (Case Study in Suka Jaya Village Muara TigaDistrict)." In order to examine three fundamental problems, namely theapplication of syirkah systems in pond management that bring prosperity andsatisfaction to pond farmers in Gampong Suka Jaya; syirkah profit sharing systemin the management of ponds in Suka Jaya Village; and whether or not the syirkahsystem is implemented according to Islamic law. The research aims to determinethe application of syirkah systems in pond management; syirkah profit sharingsystem; and to know the syirkah system among the Suka Jaya community hasbeen carried out according to Islamic law. This study uses descriptive methods,and in obtaining data in the field the author uses several ways, namely fieldresearch (Field Research), using observation, questionnaires, interviews, anddocumentation, as well as Research Library (Library Research). The resultsshowed that the implementation of syirkah cooperation carried out by theGampong Suka Jaya community in the management of ponds gave good resultsbecause the syirkah system could be a blessing by bringing satisfaction to bothparties and can improve welfare in work. Because the implementation of syirkahcarried out by the Gampong Suka Jaya community is in accordance with Islamiclaw.